2020
DOI: 10.1038/s41598-020-59652-6
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial effects of low-temperature plasma generated by atmospheric-pressure plasma jet are mediated by reactive oxygen species

Abstract: Emergence and spread of antibiotic resistance calls for development of non-chemical treatment options for bacterial infections. Plasma medicine applies low-temperature plasma (LTP) physics to address biomedical problems such as wound healing and tumor suppression. LTP has also been used for surface disinfection. However, there is still much to be learned regarding the effectiveness of LTP on bacteria in suspension in liquids, and especially on porous surfaces. We investigated the efficacy of LTP treatments aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
94
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(101 citation statements)
references
References 38 publications
(50 reference statements)
7
94
0
Order By: Relevance
“…[169,171] Due to the potent antimicrobial nature of ROS and RNS resulting from NTP, plasma treatment has been successfully used to decontaminate soil or treat it for fungal diseases, F I G U R E 5 Molecular responses of bacteria from exposure to ROS and RNS resulting from plasma treatment mostly through direct treatment of soil to generate O 3 . [158] Although there is little known so far about the effects of PTW on agricultural soils, recent studies have demonstrated that the application of PTW to solid and porous surfaces (which would be relevant to soils) effectively inhibits both Gram-negative (E. coli) and Gram-positive bacteria (Staphylococcus aureus), [174] and the PTW antimicrobial effects were shown to result from the presence of both ROS and RNS. [175] Direct plasma exposure of soils (andosol) reduced the viability of bacteria and fungi with increased efficacy at higher concentrations of O 3 (no viable bacterial or fungal colony-forming units (CFU) were detected on plate assays after soils were exposed to an O 3 dose rate of 11.6%).…”
Section: Microbiome: Interactions With Ptw and Soil For Robust Planmentioning
confidence: 99%
“…[169,171] Due to the potent antimicrobial nature of ROS and RNS resulting from NTP, plasma treatment has been successfully used to decontaminate soil or treat it for fungal diseases, F I G U R E 5 Molecular responses of bacteria from exposure to ROS and RNS resulting from plasma treatment mostly through direct treatment of soil to generate O 3 . [158] Although there is little known so far about the effects of PTW on agricultural soils, recent studies have demonstrated that the application of PTW to solid and porous surfaces (which would be relevant to soils) effectively inhibits both Gram-negative (E. coli) and Gram-positive bacteria (Staphylococcus aureus), [174] and the PTW antimicrobial effects were shown to result from the presence of both ROS and RNS. [175] Direct plasma exposure of soils (andosol) reduced the viability of bacteria and fungi with increased efficacy at higher concentrations of O 3 (no viable bacterial or fungal colony-forming units (CFU) were detected on plate assays after soils were exposed to an O 3 dose rate of 11.6%).…”
Section: Microbiome: Interactions With Ptw and Soil For Robust Planmentioning
confidence: 99%
“…However, the antibacterial effects of LTP, which are intermediated by ROS, do not show to increase bacterial resistance when bacteria are continuously exposed to it. These findings indicate that LTP is potentially a good candidate for in vivo antibiotic treatments [12][13][14].…”
Section: Introductionmentioning
confidence: 72%
“…The APPJ discussed here is also relevant for a variety of other applications which we will briefly mention. The strong abundance of reactive oxygen species make this system ideal for the applications such as cancer treatment, wound healing and antibiotic treatment 34 , 35 . In particular, the excimer was found to be the most efficient in sterilizing Bacillus stearothermophilus spores in spite of the low concentration 15 .…”
Section: Resultsmentioning
confidence: 99%